2003
DOI: 10.1212/01.wnl.0000068022.05644.01
|View full text |Cite
|
Sign up to set email alerts
|

Use of preoperative functional neuroimaging to predict language deficits from epilepsy surgery

Abstract: Preoperative fMRI predicted naming decline in patients undergoing left anterior temporal lobectomy surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
237
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(256 citation statements)
references
References 28 publications
13
237
2
4
Order By: Relevance
“…Correct localization and lateralization of language functions in patients undergoing surgical treatment of epilepsy is of utmost importance, as patients who undergo surgery in the language-dominant hemisphere are known to suffer from word finding deficits. The possibility of such deficits may be predicted by fMRI with the SDTD task [26,48]. These and our results confirm the utility of fMRI in presurgical evaluation of patients with pharmacoresistant epilepsy and add to the growing body of evidence that fMRI can be used for presurgical language localization.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Correct localization and lateralization of language functions in patients undergoing surgical treatment of epilepsy is of utmost importance, as patients who undergo surgery in the language-dominant hemisphere are known to suffer from word finding deficits. The possibility of such deficits may be predicted by fMRI with the SDTD task [26,48]. These and our results confirm the utility of fMRI in presurgical evaluation of patients with pharmacoresistant epilepsy and add to the growing body of evidence that fMRI can be used for presurgical language localization.…”
Section: Discussionsupporting
confidence: 83%
“…Some of the more recent studies used a combination of fMRI tasks for evaluation of language functions in patients with epilepsy, and at least one study proposed using fMRI instead of the IAP [33,49]. Furthermore, one fMRI study using the SDTD task in patients with left temporal lobe epilepsy has already shown 100% sensitivity and 73% specificity in predicting significant naming decline after epilepsy surgery when language was lateralized to the left hemisphere, confirming the clinical utility of this fMRI task in presurgical evaluation of epilepsy surgery patients [26]. We extended the results of the preceding studies by adding a comparison of the two most frequently used fMRI tasks and by demonstrating the excellent ability of both tasks in language localization and a strong correlation between fMRI and the IAP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…With this protocol, a key study found decline of more than two standard deviations in naming skill (relative to controls) could be predicted with 100% sensitivity and 73% specificity, with prediction superior to that using Wada (92% and 45%, respectively) [Sabsevitz et al, 2003]. Overall, 41% of variance in post-operative language skill was predicted by fMRI and the positive predictive value was 81% for fMRI and 67% for Wada.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Language functional magnetic resonance imaging (fMRI) is an imaging method and neurocognitive assessment validated for predicting language decline after temporal lobe surgery (Bonelli et al, 2012; Sabsevitz et al, 2003). The demonstration of its equivalence or superiority to the Wada test (Intracarotid Amobarbital Testing; IAT) with certain protocols (Janecek et al, 2013), and its noninvasive nature, has led to its widespread adoption in neurosurgical planning.…”
Section: Introductionmentioning
confidence: 99%